Hemostasis in Acute and Chronic Liver Disease - Tripodi, Armando (Seminars in Liver Disease, 2017)
Acute and chronic liver diseases have long been considered prototypes of acquired hemorrhagic diseases. Over the last decade, evidence stemming from the laboratory bench and clinical practice has indicated that hemostasis abnormalities, until recently considered as the cause of bleeding in these conditions, are rebalanced to normal despite the abnormal results of the hemostasis tests such as prothrombin time and platelet counts. Consequently, the commonly used therapeutic approach—the infusion of plasma, platelets, or other prohemostatic agents—are not biologically plausible and should be reconsidered. In this article, the author reviews the evidence supporting the changing paradigm.
Keywords: hypocoagulability; hypercoagulability; thrombosis; hemorrhage